Pengaruh Model Pembelajaran TPS Berbasis Pembelajaran Diferensiasi Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa Pada Materi Klasifikasi Makhluk Hidup - Adinda Givinia Rintang; Herry Sumampouw; Mariana Rengkuan (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This research aims to discuss the influence of the Think Pair Share (TPS) learning model based on differentiation learning on students' high-level thinking abilities in the material of classification of living creatures at SMP N 4 Dumoga. This research design uses an experiment with a Posttest-Only Control Group Design research design. The research was carried out in class VII with a total of 50 students divided into two groups, namely VII A as the experimental class and class VIIB as the control class. Test high-level thinking skills in the form of analysis, evaluation, and creation questions. The results of hypothesis testing using the t-test obtained tcount = 4.306 > ttable = 2.010 at α = 0.05, which means H0 is rejected and H1 is accepted. The conclusion is that there is a significant influence of the Think Pair and Share (TPS) learning model based on Differentiated Learning on Higher Level Thinking Abilities. Students think at a higher level at SMP N 4 Dumoga.